Magma Petrogenesis Study Based on Morphology and Texture Of Zircon Minerals: Case Study At The Causative Intrusive In The HLE Porphyry Copper-Gold Prospect, Sumbawa Island, Indonesia - Fadlin; Sulistyawan, Raden Isnu Hajar; Idrus, Arifudin; Asfaro, Raden Muhammad; Nhatinombe, Hernani Vitorino; Hamzah, Wildan Nur (UIR PRESS, 2024)
The zircon mineral is one of the accessory minerals within igneous rocks for its ability to resist hydrothermal and metamorphic processes. By examining their morphology and texture, zircon minerals can provide valuable insights into magma's petrogenesis, including temperature and composition. Two methods used to reach the research objectives include Petrography and SEM-CL analysis of the zircon grain from the diorite porphyry of the HLE prospect. On the basis of Petrography observation, the grain size of zircon ranges from 50 to 300 µm in size, and most have a transparent to grey color with prismatic, non-prismatic euhedral-subhedral elliptical, and non-prismatic rounded in shape. The zircon crystal typologies from the diorite porphyry are classified into S10, P2, S12, S13, S16, and S17 types, indicating the wide range of the crystallization temperature of zircon, ranging from 700 to 800 °C. The zircon from the diorite porphyry of the HLE prospect shows the medium values of pyramids typology, which is 101 = 211. It corresponds to a medium Al/Na + K ratio (A index) value, indicating zircon as a product from the calc-alkaline magmas series. The trend of the calc-alkaline/sub-alkaline in typology suggests crustal sources mixed with mantle material. Furthermore, based on SEM-CL analysis the zircon shows dominantly oscillatory zoning with thin bands, and some grains show weak zoning in the outer core, typical of magmatic zircon. Moreover, the presence of lamellae texture of magnetite-ilmenite mineral under the scanning electron microscopy (BSE image) can be interpreted as the magma related to the high oxidizing magma.